Characterization of Mechanical Oscillations in Bismuth Selenide Nanowires at Low Temperatures - Jasulaneca, Liga; Poplausks, Raimonds; Prikulis, Juris; Dzene, Elza; Yager, Tom; Erts, Donats (MDPIO, 2023)
A single transistor preamplifier circuit was designed to facilitate electrical detection of mechanical oscillations in nanoelectromechanical systems (NEMSs) at low temperatures. The amplifier was integrated in the close vicinity of the nanowire inside the cryostat to minimize cabling load and interference. The function of the circuit was impedance conversion for current flow measurements in NEMSs with a high internal resistance. The circuit was tested to operate at temperatures as low as 5 K and demonstrated the ability to detect oscillations in double-clamped bismuth selenide nanowires upon excitation by a 0.1 MHz–10 MHz AC signal applied to a mechanically separated gate electrode. A strong resonance frequency dependency on temperature was observed. A relatively weak shift in the oscillation amplitude and resonance frequency was measured when a DC bias voltage was applied to the gate electrode at a constant temperature. --//-- This is an open access article Jasulaneca, L.; Poplausks, R.; Prikulis, J.; Dzene, E.; Yager, T.; Erts, D. Characterization of Mechanical Oscillations in Bismuth Selenide Nanowires at Low Temperatures. Micromachines 2023, 14, 1910. https://doi.org/10.3390/mi14101910 published under the CC BY 4.0 licence.
This research was funded by the Latvian Council of Science, project no. lzp-2019/1-0349. L. J. acknowledges the support of the University of Latvia patron “MikroTik”. The patron’s donations are administered by University of Latvia Foundation. L. J. acknowledges funding from the project “Strengthening of the capacity of doctoral studies at the University of Latvia within the framework of the new doctoral model”, identification No. 8.2.2.0/20/I/006.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; resonance detection; radio-frequency; 1D nanomaterials; bismuth selenide